H.E.S.S. observations of the flaring gravitationally lensed galaxy PKS 1830–211. Issue 3 (20th April 2019) - ,; Abdalla, H; Aharonian, F; Ait Benkhali, F; Angüner, E O; Arakawa, M; Arcaro, C; Armand, C; Arrieta, M; Backes, M; Barnard, M; Becherini, Y; et al.
ABSTRACT: PKS 1830–211 is a known macrolensed quasar located at a redshift of z  = 2.5. Its high-energy gamma-ray emission has been detected with the Fermi- Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830–211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi- LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20–27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of ∼67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi- LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830–211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi- LAT flare spectrum.